Toonytools in Teaching Narrative Text: Pre Service Teachers' Experience - Septiyani, Dinda Nur Hanifah; Safriyani, Rizka; Asmiyah, Siti (IJET (Indonesian Journal of English Teaching), 2020)
Abstract. Technology has many applications in the field of media for teaching and learning. In private education, teachers have to be creative in creating interactive teaching media. Moreover, teaching media are needed to support the success of teaching and learning processes. Comics is favorable to read because it is fun. Online comics become popular in remote learning because students work a lot with online applications today. Toonytools is one of the favorable online comic creators. This study aims to investigate the use of Toonytools as a teaching medium in teaching Narrative Text. This study uses mix-method. A survey as a quantitative and qualitative interview was done to the students and the English Teacher. Some possible benefits and challenges within the implementation are suggested. The finding of this research is the effectiveness of using the online comic platform Toonytools, a learning media to teach the narrative text. This platform is easy to use and applied to make Toonytools feasible as a favorite online comic platform for teachers to create learning media.